Confocal laser imaging in neurosurgery: A comprehensive review of sodium fluorescein-based CONVIVO preclinical and clinical applications - Restelli, Francesco; Mathis, Andrea Maria; Höhne, Julius; Mazzapicchi, Elio; Acerbi, Francesco; Pollo, Bianca; Quint, Karl (Frontiers in Oncology, 2022)
Due to the established correlation that exists among extent of resection and postoperative survival, the achievement of complete resections is of primary importance in brain tumor surgery. Among various tools that have recently been included in current clinical practice, histopathological analysis remains the gold-standard for diagnosis. Frozen section still represents the most used, rapid, and precise intraoperative histopathological method that permits an intraoperative differential diagnosis. Unfortunately, such techniques have some intrinsic limitations, limiting its potential for obtaining real-time intraoperative diagnosis. Confocal laser technology has been recently suggested as a promising method to obtain near real-time intraoperative histological data in neurosurgery, due to its established use in other non-neurosurgical fields. Still far to be widely implemented in current neurosurgical clinical practice, pertinent literature is growing quickly, and various reports have recently demonstrated the utility of this technology in both preclinical and clinical settings in identifying brain tumors, microvasculature, and tumor margins, when coupled to the intravenous administration of sodium fluorescein. Specifically in neurosurgery, among different available devices, the ZEISS CONVIVO system probably boasts the most recent and largest number of experimental studies assessing its usefulness, which has been confirmed for identifying and classifying brain neoplasms, discerning between normal and pathologic tissue, and studying brain vessels. This systematic review has the main objective of presenting a state-of-the-art summary on actual sodium fluorescein-based preclinical and clinical applications of the ZEISS CONVIVO in neurosurgery.